DAMPAK KERUSAKAN EKOSISTEM MANGORVE TERHADAP KONDISI EKONOMI MASYARAKAT DI KABUPATEN LANGKAT (Studi Kasus Masyarakat Di Sekitar Kawasan Ekowisata Mangrove Beras Basah): (Studi Kasus Masyarakat Di Sekitar Kawasan Ekowisata Mangrove Beras Basah) - Sitepu, Dermawanta; Zahari Zen; Mardiana, Siti (JURNAL AGRICA, 2024)
The rampant planting and expansion of oil palm plantations and the construction of charcoal kitchens in Langkat Regency has caused damage to mangroves around the coast, which have the status of protected forest areas. The aim of this research is to examine the impact of mangrove damage and the potential for ecotourism development in an effort to find solutions for conservation efforts and poverty alleviation of fishermen and to study socio-economic obstacles to developing ecotourism so that mangrove damage does not continue. This research is in the form of qualitative and quantitative descriptive. This research was conducted in the Mangrove Ecotourism area in Beras Basah Village, Pangkalan Susu District, Langkat Regency, a sample of 82 residents was used. The analysis technique used in this research is two regression models looking at the influence of the independent variable on the dependent variable, namely the poverty rate and unemployment rate. The results of this research show that mangrove damage, the number of charcoal kitchens and the number of fish catches partially influence the poverty rate and unemployment rate in the Beras Basah Mangrove Ecotourism Area. Ecotourism is the right solution to maintain the mangrove ecosystem while improving the economic level of the Langkat community, especially the Beraswet Village.